IMPACT OF SHIFT WORK ON CIRCADIAN RHYTHM AND THE RISK OF CHRONIC DISEASES - Katarzyna Karaś,; Dawid Nowicki,; Małgorzata Muszyńska,; Julia Surowaniec,; Sylwia Mroszczyk, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Aim of the Study: Shift work, especially night shifts, disrupts the circadian rhythm, causes sleep disturbances, and alters hormonal and metabolic function. These disturbances are associated with an increased risk of metabolic syndrome, type 2 diabetes, cardiovascular diseases, and mental health disorders. This study aims to present the current knowledge on the impact of shift work on circadian rhythm and the risk of chronic diseases.Review Methods: The review draws on evidence identified through searches of PubMed, Web of Science, and Scopus using predefined keyword combinations related to shift work, circadian rhythms, and metabolic, cardiovascular, and psychiatric outcomes. The selection process prioritizes original studies of adult workers with clearly defined shift-work exposure and uses review articles primarily to explain biological mechanisms and outline theoretical frameworks.Summary of Current Knowledge: Studies indicate that shift work is associated with shortened and fragmented sleep, circadian desynchronization, adverse blood pressure patterns, and elevated inflammatory markers. Numerous cohort studies have found higher rates of metabolic syndrome and type 2 diabetes among shift workers compared with daytime workers, as well as more severe depressive and anxiety symptoms among night-shift workers.Conclusion: Shift work is an important, modifiable risk factor for circadian rhythm disturbances and chronic diseases. Study findings justify reducing exposure to night shifts, optimizing work schedules, and implementing preventive programs to improve sleep, lifestyle, and early detection of cardiometabolic complications.